PHYTOCHEMICAL INVESTIGATION OF TERMINALIA BELLIRICA FRUIT INSIDE - HAZRA K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The fruit of Terminalia bellirica Roxb. or Baheda (Family Combretaceae) is an extensively used herb in traditional medicines. The fruit as a whole or a part of it is used in traditional healing. Fruit has two major parts, namely, pericarp and seed, pericarp, in turn, consists of epicarp, mesocarp, and endocarp. Ayurvedic compound formulations such as Triphala and Pathyadi contain pericarp of the fruit. The present study is aiming a comparative phytochemical investigation of fruit parts such as epicarp, mesocarp, and seed along with the whole fruit. Methods: The study included physicochemical evaluation, phytochemical screening, biochemical assay, and thin-layer chromatography profile of the inner parts of the fruit. Results: The study shows that seeds are rich in essential oil (13.25%), but very poor quantity of phenolics (0.65 gallic acid equivalent [GAE]) and flavonoids (0.77 quercetin equivalent [QE]) is present compared to epicarp (139.05 GAE and 141.26 QE) and mesocarp (135.23 GAE and 142.05 QE). In addition to that, qualitative phytochemical screening revealed that seeds are void of steroids and lignans. Conclusion: The study concluded that seeds are less important in respect to the presence of secondary metabolites. It may also be concluded that mesocarp and epicarp are holding major responsibilities of therapeutic values imposed on the fruit.